Collaboration for Educational Public Policy Making in Nepal in COVID 19 Post-Pandemic Era: A Marketing Perspective - Bhakta Joshi, Umesh (Policy & Governance Review, 2025)
The COVID 19 pandemic creates a situation where innovation/expertise should be incorporate in public decisions promptly. Civil servants should bring such decisions into effect immediately. Thus, COVID 19 pandemic stresses revisiting the roles of politicians, bureaucrats and experts. However, to what extent politicians, bureaucrats and experts are collaborating for the sake of innovative ideas for policy making in COVID 19 post pandemic era in Nepal is limited exploration in Nepal eventhough government of Nepal (GoN) has been carrying out reformation efforts since 1950s and continuing till date. In this purview, this paper aims to explore higher education’s contributions to make public policy from socio-administrative perspective. The research methodology is guided by case study based. Documents of public service Commission, Nepal (PSC) and University Grants Commission, Nepal were reviewed to identify aspirants to join in civil servants at one hand. On the other hand, the teaching methods, syllabuses of Master’s level, research activities, and eventually developed policy briefs were collected from Dean offices of the University and research centres of university to find out the areas where Universities of Nepal provided innovative policy suggestions to government Nepal in administrative reform areas. Finally, interview with deans of Arts and Humanity Faculty and Management Faculty and Research Directorate, department head, secretary of Ministry of Federal Affairs and General Administration (MOFAGA)- central personnel agency were carried out. Besides, questionnaire survery was carried out to 330 respondents identified from UGC report. The research paper concluded that University contributed theoretical understanding of administrative management effectively whereas limited contributions in strategic areas of public administration.